The expectations and acceptability of a smart nursing home model among Chinese older adults and family members: a qualitative study - YuanyuanZhao, Zhao; Sazlina, Shariff-Ghazali; Rokhani, Fakhrul Z.; Jing, Su; Chew, Boon-How (Elsevier, 2023)
Purpose This study aims to explore the expectations and acceptability of a smart nursing home model among Chinese older adults and their family members based on a scoping review that defines the concept of smart nursing homes. Methods A qualitative case study was employed for this research. Semi-structured, in-depth interviews and focus group discussions were conducted on WeChat. Participants were purposively sampled through snowball sampling in Hainan and Dalian, China. A total of 28 older adults aged 60–75 and six adult children were interviewed until data saturation was achieved, followed by a thematic analysis. Results The expectations of smart nursing homes include: 1) quality of care supported by governments and societies; 2) smart technology applications; 3) the presence of a skilled healthcare professional team; 4) access to and scope of basic medical services; and 5) integration of medical services. The acceptability of smart nursing homes included factors such as stakeholders’ perceived efficaciousness, usability, and collateral damages of using smart technologies, and the coping process of adoption was influenced by factors such as age, economic status, health status, education, and openness to smart technologies among older adults. Conclusions Chinese older adults and their family members have a positive perception of the smart nursing home model. The qualitative evidence regarding their expectations and acceptability of smart nursing homes contributes valuable insights for a wide range of stakeholders involved in the planning and implementation of smart nursing homes.